Poética da prudência: a expansão portuguesa quinhentista na tradição épica - Felipe, Cleber Vinicius do Amaral (2012)
The Catholic epics of the sixteenth century, in general, showed how the men, with prudence, could serve a providential purpose. Instruments of the king and, by extension, of God, these men, worthy of everlasting song, are references for an adequate and promising future. The epic poetry shows the trajectory of a life whose example should be applied to any situation. In other words, their conduct would be widespread and universally accepted because it retrieves the best of humanity. We intend to investigate how the epics Os Lusíadas (1572), by Camoes, and Prosopopeia (1601), by Bento Teixeira, invents the act of prudence for transform it into an example to be imitated by the public.